2021
DOI: 10.3233/nre-210088
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of upper limb spasticity with inhibitory repetitive transcranial magnetic stimulation: A randomized placebo-controlled trial

Abstract: BACKGROUND: Upper limb dysfunction is a frequent complication after stroke impairing outcome. Inhibitory repetitive transcranial magnetic stimulation (rTMS) applied over the contralesional hemisphere is supposed to enhance the positive effects of conventional rehabilitative treatment. OBJECTIVE: This double-blind randomized placebo-controlled trial investigated whether inhibitory rTMS as add-on to standard therapy improves upper limb spasticity. METHODS: Twenty-eight patients (aged 44 to 80 years) with unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Through the final full-text review, 14 articles were ultimately included for this review. This study included eight research articles [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] on rTMS, one of which included three data sets, one article included two data sets and the other articles each had one data set. A total of 128 patients received rTMS in all studies, and 104 patients served as the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the final full-text review, 14 articles were ultimately included for this review. This study included eight research articles [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] on rTMS, one of which included three data sets, one article included two data sets and the other articles each had one data set. A total of 128 patients received rTMS in all studies, and 104 patients served as the control group.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies included in this meta-analysis, most of the brain regions stimulated by NIBS were the primary motor cortex [ 22 , 27 , 28 , 30 ], and a few studies were stimulated in the premotor cortex [ 23 , 30 ] and cerebellum [ 40 ]. The premotor cortex plays an important role in motor control and is another stimulation target besides the primary motor cortex [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of some pharmacological agents (e.g., monoaminergic drugs) that have an impact on motor cortex excitability and plasticity could be investigated [ 19 ]. The neuromodulation of M1 using non-invasive techniques such as transcranial direct current stimulation (tDCS) or transcranial magnetic stimulation (TMS) has also shown some promising results and should also be further assessed [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 1. 10.3389/fncir.2022.973561 Zhang et al, 2020;Gottlieb et al, 2021;Mendonca et al, 2021;Xu R. et al, 2021;Yang, 2021;Zhao, 2021;Cheng et al, 2022;Xia et al, 2022b;Yang and Yang, 2022;Zang et al, 2022) was rated as "high risk of bias" and twelve studies (Valle et al, 2007;Benito et al, 2012;Liao et al, 2015;Askin et al, 2017;Qin et al, 2018a,b;Watanabe et al, 2018;Korzhova et al, 2019;Liu et al, 2019;Chen et al, 2021;Liang et al, 2021;Xia et al, 2022a) were considered as "some concerns. "…”
Section: The Characteristics Of Included Studiesmentioning
confidence: 99%
“…Among forty-two included studies, eleven studies (Valle et al, 2007;Yan, 2015;Askin et al, 2017;Li, 2017;Kong, 2018;Tao and Wei, 2018;Dos Santos et al, 2019;Qi, 2020;Chen et al, 2021;Mendonca et al, 2021;Xu R. et al, 2021) reported that all patients could tolerate rTMS without complications, and no serious adverse effects were occurred. Seven studies (Kumru et al, 2010(Kumru et al, , 2016Benito et al, 2012;Luo, 2020;Gottlieb et al, 2021;Xia et al, 2022a,b) described that 33 patients complained of twitching facial muscles, headache, pain in contralateral hand, dizziness, neck pain, and mild drowsiness after the rTMS treatment. The rest studies did not mention any adverse effects during rTMS treatment.…”
Section: Adverse Eventsmentioning
confidence: 99%